Visual harmony : proportion in graphic design - Lin, Gengli (Gingko Press, 2015)
"Effective visual communication is not an accidental occurrence, but the result of serious intention on the part the designer to balance all aspects of the design. This is often achieved through careful application of proportion based on certain guiding principles long in existence: the golden ratio, or divine proportion, and the Fibonacci sequence. Both mathematical constructs that mirror patterns found throughout nature, from leaves and shells to sunflowers and pinecones. Artists and designers have made use of these principles for centuries to create work with long lasting appeal, from renaissance paintings to modern logos. Following a practical overview, Visual Harmony presents a survey of contemporary graphic design that all exhibits this masterful use of proportion"--Resumé vydavatele
Obsahuje rejstřík
Keywords: grafický design; vizuální komunikace; loga; geometrické proporce; graphic design; visual communication; logos (symbols); geometric proportions; příručky; handbooks and manuals